Peran Pendidikan Agama Islam Dalam Membentuk Karakter Peserta Didik di Era Digital - Syafira Corina; Nesa Putri; Suci Ariska; Gusmaneli (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study aims to examine the role of Islamic religious education in shaping students' character in the digital era. This research involves a literature review by exploring relevant research results and articles, and identifying implications for the world of education. The results show that Islamic religious education plays a crucial role in shaping students' character in the digital era. In the context of the digital era, Islamic religious education not only teaches religious values but also involves ethical and moral learning for students. This study reveals that Islamic religious education is able to teach students moral values, develop digital ethics, and build spiritual awareness in the use of technology. This research is important for educational institutions and teachers to know and understand so they can develop effective strategies for shaping students' character to be responsible, ethical, and possess integrity in life in this digital era.